Deathwatch : American film, technology, and the end of life - Combs, C. Scott (Columbia University Press, 2014)
While cinema is a medium with a unique ability to 'watch life' and 'write movement, ' it is equally singular in its portrayal of death. This book considers movie sequences in which the process of dying becomes an exercise in legibility and exploration for the camera and connects the slow or static process of dying to formal film innovation throughout the 20th century.
Keywords: Death in motion pictures.; Mortality in motion pictures.; Motion pictures -- United States -- History and criticism.; Mort au cinéma.; Mortalité au cinéma.; Cinéma -- États-Unis -- Histoire et critique.; PERFORMING ARTS -- Reference.; PHILOSOPHY -- Aesthetics.; Death in motion pictures; Mortality in motion pictures; Motion pictures; United States; Electronic books.; Criticism, interpretation, etc.